PERJANJIAN SEBAGAI DASAR PENGELOLAAN OBYEK WISATA OLEH DESA ADAT DI KABUPATEN GIANYAR - I Nyoman Punduh (Fakultas Hukum Universitas Dwijendra, 2020)
Abstrak Tourism is one of the mainstays in foreign exchange earnings for national and regional development. For this reason, Indonesia's tourism development must be able to create new innovations to sustain and increase competitiveness in a sustainable manner. At present both at the central and regional levels are regulated according to what is stated in the 1945 Constitution of the Republic of Indonesia Article 18 paragraph (2) states that